Feminist political ecology and legal geography: A case study of the Tonle Sap protected wetlands of Cambodia. (August 2019) - Gillespie, Josephine; Perry, Nicola
Legal geography (LG) unravels the co-constitutive relationship between law, space and society. Much LG scholarship has focused on urban issues situated in the Global North, but there is an emerging scholarship that explicitly extends this effort to the Global South and to rural locations. For example, Gillespie's LG research in Southeast Asia exposes problems in governance institutions and decision-making processes that can unintentionally exacerbate existing socioeconomic disadvantage. The feminist political ecology (FPE) approach, as conceptualized by Rocheleau et al. and more recently expanded upon by Elmhirst provides a useful additional framework for considering the intersectionality of social and environmental factors which constitute identity, and the mutual dependency between identity and ecological processes. In this paper we argue that marrying an LG perspective with FPE results in a more nuanced understanding of complex legal–human–environment dynamics. Our focus on lore/law plus gendered identity as a lens for analysis blends an emergent LG literature with insights from FPE. This paper draws on research from a pilot project on the formal and informal regulatory mechanisms that enable and/or disable sustainable conservation in the protected wetlands of the Tonle Sap (lake) in central Cambodia.